Equilibrium Real Effective Exchange Rates and Real Exchange Rate Misalignments: Time Series vs. Panel Estimates - Oliver Hossfeld (FIW - Research Centre International Economics, 2010)
We follow the behavioral equilibrium exchange rate approach by Clark and MacDonald (1998) to derive equilibrium real effective exchange rates and currency misalignments for the US and its 16 major trading partners. We apply cointegration and panel cointegration techniques to derive fully countryspecific measures of misalignment and measures based on panel estimates. We formally test the forecast performance of pooled vs. heterogeneous estimators over a hold-back period and find that pooling the data delivers more accurate forecasts in the vast majority of cases although the implicit long-run homogeneity restriction is statistically rejected. This is especially remarkable, since we have given the heterogeneous estimator an 'unfair' advantage by choosing the country-specific model (of up to 21 possible ones) with the best out-of-sample performance prior to comparing it to two final panel specifications. Robustness of the results is supported by recently introduced cross-sectionally augmented panel unit root tests by Pesaran (2007) and bootstrapped error correction-based panel cointegration tests by Westerlund (2007), as well as different estimators. While we find strong evidence for the Balassa-Samuelson-effect, the evidence for other commonly hypothesized fundamentals is weak.
Keywords: C22; C23; F31; F37; 330; behavioral equilibrium exchange rate; real exchange rate misalignment; panel cointegration; CIPS test; cross-sectional dependence; exchange rate forecasts; exchange rate fundamentals